The Annotated Hunting of the snark : the full text of Lewis Carroll's great nonsense epic The hunting of the snark - 4 0 16; 1914-2010.;1832-1898. Gardner, Martin,;Carroll, Lewis; 5 (New York : W.W. Norton, 2006)
An annotated edition of Lewis Caroll's 1876 poem Hunting of the Shark with insights into Caroll's use of fancy and philosophy, information on the poem's publishing, and original illustrations to accompany the text.
Hunting of the Snark: an agony in eight fits, by Lewis Carroll, illustrated by Henry Holiday --;Dedicatory poem --;Fit the First, The Landing --;Fit the Second, The Bellman's Speech --;Fit the Third, The Baker's Tale --;Fit the Fourth, The Hunting --;Fit the Fifth, The Beaver's Lesson --;Fit the Sixth, The Barrister's Dream --;Fit the Seventh, The Baker's Fate --;Fit the Eighth, The Vanishing --;An Easter Greeting --;Peter Newell's Snark illustrations --;A Commentary by Snarkophilus Snobbs [F.C.S. Schiller] --;Clue, A Sequel by J.A. Lindon --;Snark's Significance by Henry Holiday --;Excerpts from Henry Holiday's Reminiscences of My Life --;Selected Bibliography --;Listing of the Snark by Selwyn H. Goodacre --;Hunting the Snark on the Web. The
Includes bibliographical references (pages 117-125)
Keywords: 2 -- Carroll, Lewis, -- 1832-1898.; 6; History and criticism. -- Nonsense verses, English -- 20; 20; Criticism, interpretation, etc